The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5194/hess-23-107-2019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the spatial dependence of floods using the Fisher copula

Abstract: Abstract. Floods often affect not only a single location, but also a whole region. Flood frequency analysis should therefore be undertaken at a regional scale which requires the considerations of the dependence of events at different locations. This dependence is often neglected even though its consideration is essential to derive reliable flood estimates. A model used in regional multivariate frequency analysis should ideally consider the dependence of events at multiple sites which might show dependence in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 68 publications
(110 reference statements)
0
51
0
Order By: Relevance
“…The Thur catchment has been the subject of several studies in the past: Gurtz et al (1999) performed the first modelling study on the entire catchment using a semi-distributed hydrological model; Abbaspour et al (2007) modelled hydrology and water quality using the SWAT model; Fundel et al (2013) and Jorg-Hess et al (2015) focused on low flows and droughts; Jasper et al (2004) investigated the impact of climate change on the natural water budget. Other modelling studies also include Melsen et al (2014Melsen et al ( , 2016, who investigated parameter estimation in data-limited scenarios and parameter transferability across spatial and temporal scales, and Brunner et al (2019), who studied the spatial dependence of floods. The Thur also includes a small-sized experimental subcatchment (Rietholzbach, called Mosnang in this paper after the name of the gauging station) that was the subject of many field studies at the interface between process understanding and hydrological modelling (e.g.…”
Section: Study Areamentioning
confidence: 99%
“…The Thur catchment has been the subject of several studies in the past: Gurtz et al (1999) performed the first modelling study on the entire catchment using a semi-distributed hydrological model; Abbaspour et al (2007) modelled hydrology and water quality using the SWAT model; Fundel et al (2013) and Jorg-Hess et al (2015) focused on low flows and droughts; Jasper et al (2004) investigated the impact of climate change on the natural water budget. Other modelling studies also include Melsen et al (2014Melsen et al ( , 2016, who investigated parameter estimation in data-limited scenarios and parameter transferability across spatial and temporal scales, and Brunner et al (2019), who studied the spatial dependence of floods. The Thur also includes a small-sized experimental subcatchment (Rietholzbach, called Mosnang in this paper after the name of the gauging station) that was the subject of many field studies at the interface between process understanding and hydrological modelling (e.g.…”
Section: Study Areamentioning
confidence: 99%
“…Flood events are identified for each of the five time series (one observed, four simulated) using a peak-over-threshold (POT) approach similar to the one used in Brunner et al (2019aBrunner et al ( , 2020b. This approach consists of two main steps and results in two data sets each, which are used for the local and spatial analysis, respectively: (1) POT events in individual catchments and 2event occurrences across all catchments.…”
Section: Flood Event Identificationmentioning
confidence: 99%
“…Despite the importance of understanding the spatial dependence of floods when deriving regional flood estimates, it has often been overlooked in practical applications and is not well understood. While the spatial dependence of precipitation has been investigated in several studies (e.g., Davison et al, 2012;Le et al, 2018;Thibaud et al, 2013;Touma et al, 2018), the spatial dependence of floods has been addressed in only a few studies primarily focused on modeling this spatial dependence under stationary conditions (Asadi et al, 2015;Bracken et al, 2016;Brunner et al, 2019;Diederen et al, 2019;Keef et al, 2009;Neal et al, 2013;Quinn et al, 2019). Asadi et al (2015) and Brunner et al (2019) have shown that the spatial dependence of floods at different locations decreases with the increase of the distance along the river network between these stations.…”
Section: Introductionmentioning
confidence: 99%